(untitled) (International Journal of Plant Biology, 2017)
There is a great interest in discovering new microbial natural biocides such as microbial secondary metabolites to reduce the environmental pollution due to the excessive use of synthetic pesticides. Verticillium wilt, caused by the soil-borne Verticillium dahliae, is a widespread disease in tomato growing in many parts of the world. Burkholderia gladioli pv. agaricicola produces some antimicrobial substances and extracellular hydrolytic enzymes which exhibited promising antimicrobial activity towards several phytopathogens. The aims of the current research are to assess in vitro fungicidal effect of 4 strains of B. gladioli pv. agaricicola (ICMP11096, 11097, 12220 and 12322) against V. dahliae using culture or cell-free culture filtrate. In situ assay was performed to evaluate the biocontrol effect of the most efficient bacterial strain on wilt disease caused by V. dahliae in tomato plants. Results demonstrated that the studied bacterial strain ICMP12322 exerted the highest in vitro antifungal activity against V. dahliae which correlated with its ability to produce extracellular hydrolytic enzymes. Furthermore, in situ results showed that the selected bacterial strain significantly minimized the disease incidence.